Theoretical foundations of formation of organizational culture of higher education institutions - S.B.; I.M. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
Modern reality in conditions of fierce competition, a high degree of uncertainty and economic instability puts forward new demands on the management of organizations and actually reorients it from extensive to intensive sources of development. It becomes obvious that in the current conditions those organizations will «survive» and will be able to function and develop in the future, which in their activities are focused not only on improving financial and economic indicators, but also on the formation of a completely new ideology of management, a new nature of connections and relations with external and internal environment, i.e. for the development of one’s culture. In view of this, in recent years, both in practice and in theory of management, it is possible to observe an increase in attention to the organizational culture of the enterprise. Organizational culture is an integral part of any organization, and in modern conditions it turns into an effective and efficient tool of strategic business development, shapes the image of the organization, allows solving numerous problems that arise in them, it is oriented towards achieving the business goals of the organization and ensuring the efficiency of its functioning. Certain conceptual ideas about organizational culture have existed for quite a long time. In recent years, in the research of domestic scientists on this issue, significant progress has been observed in understanding the essence of organizational culture, its role and significance for the internal integration and development of the organization. At the same time, dynamic changes and the development of the competitive environment require the analysis of organizational culture from the point of view of not only the internal processes of the organization, but also its role in creating and strengthening competitive advantages.